2012
DOI: 10.1007/s00213-012-2852-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of AMPA receptor blockade in the prelimbic cortex on systemic and ventral tegmental area opiate reward sensitivity

Abstract: These findings suggest a critical role for intra-PLC AMPA receptor transmission in the processing of opiate reward signaling. Furthermore, blockade of AMPA transmission specifically within the PLC is capable of switching opiate reward processing to a DA-dependent reward system, independently of previous opiate exposure history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…However, although both electrical stimulation of the NI and CRF infusion into the NI produced inhibition of mPFC activity, the current study does not exclude the possibility that CRF diffused to other structures. The mPFC in the rodent is implicated in a variety of cognitive processes such as spatial memory, possibly as a function of working memory, consolidation of long‐term memory, memory retrieval (Granon & Poucet, ; Seamans et al ., ; Delatour & Gisquet‐Verrier, ; Laroche et al ., ), expression of conditioned fear memory (Burgos‐Robles et al ., ) and drug addiction (see Lüscher & Malenka, for a review; De Jaeger et al ., ). It is possible that the inhibition of neurons in the mPFC, due to CRF infusion/electrical stimulation of the NI, affects these cognitive processes.…”
Section: Discussionmentioning
confidence: 97%
“…However, although both electrical stimulation of the NI and CRF infusion into the NI produced inhibition of mPFC activity, the current study does not exclude the possibility that CRF diffused to other structures. The mPFC in the rodent is implicated in a variety of cognitive processes such as spatial memory, possibly as a function of working memory, consolidation of long‐term memory, memory retrieval (Granon & Poucet, ; Seamans et al ., ; Delatour & Gisquet‐Verrier, ; Laroche et al ., ), expression of conditioned fear memory (Burgos‐Robles et al ., ) and drug addiction (see Lüscher & Malenka, for a review; De Jaeger et al ., ). It is possible that the inhibition of neurons in the mPFC, due to CRF infusion/electrical stimulation of the NI, affects these cognitive processes.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the VTA also sends DAergic projections directly to the mPFC [41], [42]. In addition, glutamatergic hypofunction directly in the mPFC potentiates opiate-related reward memory through DA-dependent substrates [15], [43] and modulation of mPFC neuronal activity via ascending BLA inputs is dependent upon DAergic signaling [44]. However, in these cases, DAergic modulation of emotionally salient memory is dependent upon functional BLA inputs, consistent with the current findings demonstrating that the BLA represents a first-order neural substrate for the processing of opiate-related associative memory.…”
Section: Discussionmentioning
confidence: 99%
“…In the VTA, the opioids can recruit dopamine cells through a disinhibitory mechanism (Johnson and North, 1992;Jalabert et al, 2011). While some authors observed no significant correlation between the VTA antero-posterior placement of morphine injection and the resulting place conditioning (De Jaeger et al, 2013), data from other groups support the idea that opioids can have different behavioral consequences depending on the anteroposterior level within the VTA (Zangen et al, 2002;Jhou et al, 2012). Indeed, endomorphin-1 (EM-1) induces intracranial self-administration, conditioned place preference and increases locomotor activity when administered into the pVTA (Zangen et al, 2002;Terashvili et al, 2004) (Fig.…”
Section: Opioidsmentioning
confidence: 96%